PARE CHIPS BUSINESS TRAINING: Increasing Competitiveness in the Digital Age - Muhamad Zen (Jurnal PKM Manajemen Bisnis, 2023)
Small and medium enterprises (SMEs) in the pare chips sector have great potential to support the local economy. However, challenges in the rapidly developing digital era require understanding and adaptation of appropriate business strategies. Therefore, this service activity aims to provide business training to SME owners of bitter melon chips in order to optimize their business competitiveness in the digital era. The main purpose of this community service activity is to increase the understanding and skills of UKM owners of bitter melon chips in dealing with the digital era. We strive to provide participants with a better understanding of leveraging digital platforms, online marketing strategies, technology-based business management, and using digital tools to increase productivity. The implementation of this activity involves several methods including presentation of entrepreneurial material, question and answer, practice and guidance. The results of this activity include increasing the understanding and skills of SME chips pare owners in implementing business strategies in the digital era. They are able to leverage social media, increase online visibility, manage inventory more efficiently, and increase their business productivity. In addition, the collaboration between the UKM owners of bitter melon chips that was established during this activity allows for the exchange of experiences and learning between people. Some of the participants even reported a significant increase in their sales after taking this training.